Analisis Pengaruh Ketersediaan Bahan Baku serta Mutu Produk Ikan Asin terhadap Keberlangsungan UMKM di Kelurahan Hajoran, Kecamatan Pandan, Kabupaten Tapanuli Tengah - Ira Sukma Panggabean; Aprinawati Aprinawati (BADAN PENERBIT STIEPARI PRESS, 2025)
This research is motivated by the problem of how the availability of raw materials and the quality of salted fish products influence the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Hajoran Village, Pandan District, Central Tapanuli Regency. The study aims to analyze the extent to which these two factors contribute to the continuity and long-term viability of MSME businesses in the region. The research uses a quantitative approach, with the population being MSME actors engaged in salted fish production in Hajoran Village. The sample consisted of 63 respondents, selected through purposive sampling, with data collected via questionnaire distribution. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS) version 26. The findings indicate that the availability of raw materials has a positive and significant effect on business sustainability, with a standardized coefficient of 0.378 and a significance level of 0.000. Likewise, product quality also shows a positive and significant influence, with a coefficient of 0.455 and the same significance level (0.000). Simultaneously, these two variables contribute a combined influence of 68.4% to the sustainability of MSMEs. The results suggest that improving access to raw materials and enhancing product quality are crucial strategies for ensuring the long-term success of MSMEs in the salted fish industry.